Synthesis and antimicrobial activity of the hybrid molecules between amoxicillin and derivatives of benzoic acid. Issue 2 (21st September 2020) - Li, Zhonglin; Lin, Hao; Zhou, Junwen; Chen, Liangzhu; Pan, Zhikun; Fang, Binghu
Abstract: Due to the increasing problem of bacterial resistance worldwide, the demand for new antibiotics is becoming increasingly urgent. We wished to: (a) prepare hybrid molecules by linking different pharmacophores by chemical bonds; (b) investigate the antib acterial activity of these hybrids using drug‐sensitive and drug‐resistant pathogens in vitro and vivo . A series of hybrid molecules with a diester structure were designed and synthesized that linked amoxicillin and derivatives of benzoic acid via a methylene bridge. Synthesized compounds were evaluated for activities against Gram‐positive bacteria ( Staphylococcus aureus American Type Culture Collection [ATCC] 29213, ATCC 11632; methicillin‐resistant S. aureus [MRSA] 11; Escherichia coli ATCC 25922) and Gram‐negative bacteria ( Salmonella LS677, GD836, GD828, GD3625) by microdilution of broth. Synthesized compounds showed good activity against Gram‐positive and Gram‐negative bacteria in vitro. In particular, amoxicillin‐ p ‐nitrobenzoic acid (6d ) showed good activity against Salmonella species and had better activity against methicillin‐resistant S. aureus (minimum inhibitory concentration [MIC] = 64 μg/ml) than the reference drug, amoxicillin (MIC = 128 μg/ml). Amoxicillin‐ p ‐methoxybenzoic acid (6b ) had the best antibacterial activity in vivo (ED50 = 13.2496 μg/ml). The hybrid molecules of amoxicillin and derivatives of benzoic acid synthesized based on a diester structure can improve the activity of amoxicillin against Salmonella species and even improve the activity against MRSA.